2020
DOI: 10.1002/adfm.202002622
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photoinduced Phase Segregation and Origin of Long Carrier Lifetime in Mixed‐Halide Perovskite Films

Abstract: Mixed-halide hybrid perovskite semiconductors have attracted tremendous attention as a promising candidate for efficient photovoltaic and lightemitting devices. However, these perovskite materials may undergo phase segregation under light illumination, thus affecting their optoelectronic properties. Here, photoexcitation induced phase segregation in triplecation mixed-halide perovskite films that yields to red-shift in the photoluminescence response is reported. It is demonstrated that photo excitation induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 49 publications
7
56
0
Order By: Relevance
“…The time‐dependent PL images of pristine CsFAMA film exhibit evolution of heterogeneity upon light illumination, indicating the formation of narrow band‐gap domains that serve as a trap for electron and hole and cause PL quenching. [ 42 ] The homogenized PL images from CsFAMA‐MCL film implies uniformity across the whole film. In addition, charge–discharge experiments also reveal faster discharge processes in CsFAMA‐MCL solar cells, further verifying the reduced ion migration in the CsFAMA‐MCL film (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The time‐dependent PL images of pristine CsFAMA film exhibit evolution of heterogeneity upon light illumination, indicating the formation of narrow band‐gap domains that serve as a trap for electron and hole and cause PL quenching. [ 42 ] The homogenized PL images from CsFAMA‐MCL film implies uniformity across the whole film. In addition, charge–discharge experiments also reveal faster discharge processes in CsFAMA‐MCL solar cells, further verifying the reduced ion migration in the CsFAMA‐MCL film (Figure S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, long-lived charge carriers also allow trapping of charge carriers at the defect sites. [48] For example, the capture of holes by halide ions (e.g., I − ) makes them mobile as the oxidized halide (I • ) is expelled from the lattice. [49] The iodide defects further assist in the movement of halide ions.…”
Section: Thermodynamics Of Phase Segregationmentioning
confidence: 99%
“…[5,17] Besides, it has been demonstrated that mixed halide perovskites suffered from phase segregation under continuous light illumination. [18,19] Han et al spun cast MACl atop FAPbI 3 to vertically recrystallize perovskites upon a small amount of MA into the crystal lattice without compromising the absorption onset. [20] However, a recent work by Yang et al showed that barely using MACl as stabilizer could maintain the α phase of FAPbI 3 .…”
Section: Doi: 101002/adma202007126mentioning
confidence: 99%